Clinical response rate and flares of hidradenitis suppurativa in the treatment with adalimumab. (1st June 2020) - Caposiena Caro, R. D.; Cannizzaro, M. V.; Tartaglia, C.; Bianchi, L.
Summary: Background: Hidradenitis suppurativa/acne inversa (HS) is a chronic, inflammatory, skin disease. adalimumab is the sole approved drug for the treatment of HS, but it only partially controls the symptoms. Aim: To evaluate the incidence of flares during 108 weeks of therapy and the clinical response to adalimumab. Methods: In total, 20 patients with moderate–severe HS treated with adalimumab were included to evaluate the number of flares, mean time interval between flares, lesion count number of patients who reached the Hidradenitis Suppurativa Clinical Response (HiSCR) of ≥ 50% reduction in inflammatory lesion count, and the International Hidradenitis Suppurativa Severity Score System (IHS4), pain visual analogue scale (VAS) and Dermatology Life Quality Index (DLQI). Results: In total, 90% of patients reported at least 1 flare, and in total 48 flares were counted for the whole group; mean time between flares was 26.9 ± 16.4 weeks. Duration between flares was 30.5 ± 16.3 and 12.5 ± 5.7, respectively, in responders and nonresponders. A progressive decline in flares was observed with treatment, while a gradual increase in the number of patients achieving HiSCR was attained during the observational period. Lesion count, IHS4, pain VAS and DLQI decreased throughout the study. In detail, adalimumab showed a higher efficacy on nodules and abscesses than on draining tunnels. The study was limited by its retrospective nature and small number of patients. Conclusion: Adalimumab is an effective and safe treatment for patients with HS despite the high number of flares.